Sediment transport analysis of Skudai River, Johore using HEC-RAS [compact disc] - 450860 Loh, Yee Teng (Skudai : Universiti Teknologi Malaysia, 2005)
Project Paper (Sarjana Muda Kejuruteraan Awam) - Universiti Teknologi Malaysia, 2005